1999
DOI: 10.1017/s0266078400011251
|View full text |Cite
|
Sign up to set email alerts
|

Forty years of official bilingualism in cameroon

Abstract: An appraisal of the promotion of a policy of official French/English bilingualism in operation since 1961

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 2 publications
0
13
0
Order By: Relevance
“…MINEDUC [3]). Other evaluations were made by a number of researchers, among others: Constable [4], Tchoungui [5], Kouega [6,2,7,8,9], Biloa [10], Echu [11], Simo Bobda [12], Ombouda Onana [13], Sokeng Piewo [14], and Kouega and Sokeng Piewo [15]. Their findings revealed that the official bilingualism policy fails to produce bilingual Cameroonians.…”
Section: Background To the Studymentioning
confidence: 99%
“…MINEDUC [3]). Other evaluations were made by a number of researchers, among others: Constable [4], Tchoungui [5], Kouega [6,2,7,8,9], Biloa [10], Echu [11], Simo Bobda [12], Ombouda Onana [13], Sokeng Piewo [14], and Kouega and Sokeng Piewo [15]. Their findings revealed that the official bilingualism policy fails to produce bilingual Cameroonians.…”
Section: Background To the Studymentioning
confidence: 99%
“…(2) What are the differences of leadership styles of principals as perceived by principals and teachers in both public and private schools? (3) What are student perceptions of the type of leadership their principal portrays?…”
Section: Research Questionsmentioning
confidence: 99%
“…This trend is notable in larger cities, especially in Yaoundé, where many Anglophone schools are overwhelmed by the high demand from Francophone parents. To this effect, Kouega [2] argued that choosing English and the Anglophone system of education by French speaking Cameroonians is because of unique advantage of the language. Achimbe [3] also ascertained that the demand for English education is not born of new positive attitudes toward English speaking Cameroonians but is instead an endeavour to benefit from the advantages related to English proficiency.…”
Section: Introductionmentioning
confidence: 99%
“…At tertiary level, students take different directions according to their chosen subjects: science-oriented students register in science faculties while arts-oriented students go to arts, law, or economics faculties (for language problems faced by Anglophone students at tertiary level in Cameroon, see among other works, Kouega, 1999aKouega, , 2007aKouega, , 2008. In short, the English language syllabus prepares the ground for learners' low performance in the spoken English skill in general and in accuracy in speaking in particular.…”
Section: English In Education In Cameroonmentioning
confidence: 99%